Studi Penyebab Gangguan dan Solusi Perbaikan Sistem Kemudi Pada Sepeda Motor HONDA CRF SERI 150L KAPASITAS 150 CC - Riki Candra Putra; Ali Rosyidin (Universitas Muhammadiyah Tangerang, 2023)
One of the vehicle systems that must be designed to provide safety and comfort while driving is a good steering system. One of the characteristics of a good steering system is the balance of the rotation of the steering system when used. At this time the problem with the steering system is the motorbike steering wheel which is difficult to balance and control due to damage to the steering area, especially on the Honda CRF type 150L motorbike. So this research will look for a solution to the problem. This research uses the method of literature study, field study, observation and discussion in the data collection process. The purpose of this study is to analyze the causes of damage to the steering wheel, make a design plan for composite fastener nuts as well as covering the steering area, and create a steering system maintenance program for the steering system area. With the results of the analysis that has been carried out on the steering system in the steering area, alternative solutions are obtained to prevent damage to the steering wheel by designing the steering wheel adjustment nut and maintaining the steering system in the steering area.